Effects of exoskeleton-assisted walking on bowel function in motor-complete spinal cord injury patients: involvement of the brain–gut axis, a pilot study - Hu, Xiaomin; Feng, Jing; Lu, Jiachun; Pang, Rizhao; Zhang, Anren; Liu, Jiancheng; Gou, Xiang; Bai, Xingang; Wang, Junyu; Chang, Cong; Yin, Jie; Wang, Yunyun; et al. (Frontiers in Neuroscience, 2024)
Evidence has demonstrated that exoskeleton robots can improve intestinal function in patients with spinal cord injury (SCI). However, the underlying mechanisms remain unelucidated. This study investigated the effects of exoskeleton-assisted walking (EAW) on intestinal function and intestinal flora structure in T2-L1 motor complete paraplegia patients. The results showed that five participants in the EAW group and three in the conventional group reported improvements in at least one bowel management index, including an increased frequency of bowel evacuations, less time spent on bowel management per day, and less external assistance (manual digital stimulation, medication, and enema usage). After 8 weeks of training, the amount of glycerol used in the EAW group decreased significantly(p ＜ 0.05). The EAW group showed an increasing trend in the neurogenic bowel dysfunction (NBD) score after 8 weeks of training, while the conventional group showed a worsening trend. Patients who received the EAW intervention exhibited a decreased abundance of Bacteroidetes and Verrucomicrobia, while Firmicutes, Proteobacteria, and Actinobacteria were upregulated. In addition, there were decreases in the abundances of Bacteroides, Prevotella, Parabacteroides, Akkermansia, Blautia, Ruminococcus 2, and Megamonas. In contrast, Ruminococcus 1, Ruminococcaceae UCG002, Faecalibacterium, Dialister, Ralstonia, Escherichia-Shigella, and Bifidobacterium showed upregulation among the top 15 genera. The abundance of Ralstonia was significantly higher in the EAW group than in the conventional group, and Dialister increased significantly in EAW individuals at 8 weeks. This study suggests that EAW can improve intestinal function of SCI patients in a limited way, and may be associated with changes in the abundance of intestinal flora, especially an increase in beneficial bacteria. In the future, we need to further understand the changes in microbial groups caused by EAW training and all related impact mechanisms, especially intestinal flora metabolites.